Korelasi Keterampilan Membaca Pemahaman Teks Laporan Hasil Observasi dan Keterampilan Menulis Teks Laporan Hasil Observasi Siswa Kelas X SMA Negeri 2 Bayang - Feronika, Niken Oktri; Gani, Erizal (Indonesian and Regional Language and Literature Department, Universitas Negeri Padang, 2024)
The research aimed to describe the level of reading comprehension skills, describe the level of writing skills, and analyze whether there was a correlation between reading comprehension skills and the skills in writing text reports from observations of class X students at SMA Negeri 2 Bayang. This type of research is quantitative research with descriptive methods. The research sample was taken at 15% using a simple random sampling technique. The instrument of this research is a test, namely an objective test of reading comprehension skills and a performance test of writing skills. There are three research results. First, the reading comprehension skills of the text of the observation report of class X students of SMA Negeri 2 Bayang are more than sufficient, with an average calculation of 67.07. Second, the skill of writing the text of the observation report of the students of class X of SMA Negeri 2 Bayang is at a sufficient qualification with an average calculation of 65.21. Third, a significant correlation exists between reading comprehension skills and observation report text writing skills with r_count>r_tabel, namely 0.976>0.297. H0 is rejected, and H1 is accepted because t_count (29.52) is greater than t_table (1.68). Thus, it can be concluded that reading comprehension skills are positively correlated with skills in writing observation report texts.